2017
DOI: 10.1089/neu.2016.4915
|View full text |Cite
|
Sign up to set email alerts
|

Compression Decreases Anatomical and Functional Recovery and Alters Inflammation after Contusive Spinal Cord Injury

Abstract: Experimental models of spinal cord injury (SCI) typically utilize contusion or compression injuries. Clinically, however, SCI is heterogeneous and the primary injury mode may affect secondary injury progression and neuroprotective therapeutic efficacy. Specifically, immunomodulatory agents are of therapeutic interest because the activation state of SCI macrophages may facilitate pathology but also improve repair. It is unknown currently how the primary injury biomechanics affect macrophage activation. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Scarring and inflammatory responses to SCI include a complex diversity of cells and cellular activities that vary based on injury type, timing, and spatial distribution [182,183]. Glial and inflammatory cells affect the injury progression with profound impacts on overall neuronal function and SCI outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Scarring and inflammatory responses to SCI include a complex diversity of cells and cellular activities that vary based on injury type, timing, and spatial distribution [182,183]. Glial and inflammatory cells affect the injury progression with profound impacts on overall neuronal function and SCI outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has not been identified as a myelin receptor in SCI, we recently observed that macrophages upregulate MARCO in response to proinflammatory stimuli and express MARCO in the injured spinal cord (Gensel, Kopper, Zhang, Orr, & Bailey, 2017;Orr et al, 2017).…”
Section: A Cr Op H Ag E R Ec Ep Tor -M Ed I At Ed M Y El I N R E mentioning
confidence: 89%
“…Thus, it is likely that MARCO can bind myelin lipids effectively. Although it has not been identified as a myelin receptor in SCI, we recently observed that macrophages upregulate MARCO in response to proinflammatory stimuli and express MARCO in the injured spinal cord (Gensel, Kopper, Zhang, Orr, & Bailey, ; Orr et al, ). MARCO activation, therefore, may be a potential mechanism for proinflammatory macrophage‐mediated myelin removal in SCI.…”
Section: Macrophage Receptor–mediated Myelin Removalmentioning
confidence: 99%
“…Spinal cord injury (SCI) causes serious disability and is a medical problem worldwide (1). SCI has two defined phases, consisting of primary and secondary injury mechanisms that lead to an excessive inflammatory response (2,3). Disruption of the spinal tract results in neuronal apoptosis, and impedes neuronal repair and regeneration.…”
Section: Introductionmentioning
confidence: 99%